THE RELATIONSHIP BETWEEN LEARNING DISCIPLINE AND SCHOOL ENVIRONMENT WITH STUDENT MATHEMATICS LEARNING OUTCOMES OF CLASS X OF SMK - Irma Andriani; Anggit Prabowo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This research was motivated by the number of students who often come late to school and the poor students' poor way of greeting teachers. This study aimed to determine whether or not the relationship between the learning discipline and school environment with the student mathematics learning outcomes of class X even semester even of the Light Vehicle Engineering Program of Muhammadiyah Vocational High School (SMK Muhammadiyah) Imogiri academic year 2017/2018 or not. The population in this research was all students of class X, even semester program of expertise of Light Vehicle Engineering SMK Muhammadiyah Imogiri academic year 2017/2018, consisting of 6 classes with 211 students. A sample was established using a random sampling of the class and obtained class X TKR 1 with an amount of student 30 people. Methods of data collection using questionnaires to obtain data of learning discipline and school environment and test instrument to obtain mathematics learning result data. The instruments were analyzed of their validity, reliability, discriminant, and difficulty. Data analysis in the form of the prerequisite test included a normality test, linearity test, and independence tests. The hypothesis test consisted of a simple linear regression test and multiple linear correlation-regression tests. The results showed a positive and significant relationship between the learning discipline and the school environment with mathematics learning outcomes of students of class X semester, even the expertise program of Light Vehicle Engineering SMK Muhammadiyah Imogiri academic year 2017/2018. This is shown by Fcount â‰¥ Ftable with R = 0,521089029 and R2 = 0.2715337761 with Å¶=13.268027 + 0,4152482X1 + 0,2961205X2, with RC X1 = 75.1%, RC X2 = 24,9%, EC X1= 20,4%, and EC X2= 6,8%.